The Routledge Handbook of Maritime Management - Panayides, Photis (My University, 2019)
This handbook provides a wide-ranging, coherent, and systematic analysis of maritime management, policy, and strategy development. It undertakes a comprehensive examination of the fields of management and policy-making in shipping by bringing together chapters on key topics of seminal scientific and practical importance. Within 21 original chapters, authoritative experts describe and analyze concepts at the cutting edge of knowledge in shipping. Themes include maritime management and policy, ship finance, port and maritime economics, and maritime logistics. A study examines the determinants of ship management fees. Aspects of corporate governance in the shipping industry are reviewed and there is a critical review of the ship investment literature. Other topics featured include the organization and management of tanker and dry bulk shipping companies, environmental management in shipping with reference to energy-efficient ship operation, a study of the BIMCO Shipping KPI standard, utilizing the Bunker Adjustment Factor as a strategic decision-making instrument, and slow steaming in the maritime industry. All chapters are written to provide implications for further advancement in professional practice and research. The Routledge Handbook of Maritime Management will be of great interest to relevant students, researchers, academics, and professionals alike. It provides abundant opportunities to guide further research in the areas covered but will also initiate and inspire effective maritime management.
Keywords: Maritime Management, Shipping